KEPEMIMPINAN NON MUSLIM MENURUT QURAISH SHIHAB DALAM KONTEKS NEGARA MODERN - Oldha Fauzia; Yulia Pratami Putri; Mayasari; Yesa Gusra Saputri (STKIP Subang, 2026)
The issue of non-Muslim leadership has become a problematic discourse in the context of interreligious relations in Indonesia, particularly for Muslims in managing socio-political and religious interactions with non-Muslim communities. This problem arises from the tension between the state constitution, which guarantees equal political rights for all citizens, and certain textual interpretations of the Qur’an that are often understood as prohibiting non-Muslim leadership. As the country with the largest Muslim population in the world, Indonesia faces a unique situation in which Muslims adhere both to the national constitution and to religious principles derived from the Qur’an. This study aims to identify the Qur’anic verses used by M. Quraish Shihab in discussing the issue of non-Muslim leadership, to analyze his interpretation of these verses, and to examine his views on non-Muslim leadership in the contemporary context. The research employs a qualitative approach based on contemporary Qur’anic exegesis, using a descriptive-analytical method to examine primary and secondary sources related to Quraish Shihab’s interpretations. The findings indicate that Quraish Shihab does not view the relevant Qur’anic verses as establishing an absolute and universal prohibition against non-Muslim leadership. Instead, he interprets them contextually, considering their historical background and socio-political circumstances. In the context of modern Indonesia, Quraish Shihab argues that appointing a non-Muslim leader is permissible as long as it brings public benefit (maslahah) and does not result in harm or injustice. However, he maintains that Muslims should ideally prioritize leaders from among the believers, while still acknowledging the legitimacy of non-Muslim leadership under certain conditions in a pluralistic society.